Friday

April 18, 2014

April 18, 2014

Posted by **ANON** on Sunday, September 30, 2012 at 2:09pm.

thus f-1(x)=2-sqrt(-x+6)

i need to show that f(f-1(x))=x, but i keep getting negative x...any help

- precalc -
**Reiny**, Sunday, September 30, 2012 at 3:28pmby definition ...

f(f^-1 (x)) = x , but anyway ...

f( f^-1(x) )

= f(2 - √(6-x) )

= 2 + 4(2 - √(6-x) ) - (2 - √(6-x) )^2

= 2 + 8 - 4√(6-x) - (4 - 4√(+-x) + 6-x)

= 10 - 4√(6-x) - 4 + 4√(6-x) - 6 + x

= x

**Related Questions**

Math - find any stationary points of the function g(x) = (2x-3)square root of 5+...

calculus - prove that d/dx 4x .√(x + √x) = 6x+5 (x)1/2/√(x...

math,help,algebra I - I need help can someone help me get unstuck and let me ...

algebra,math,help - Use Property 2 to simplify each of the following radical ...

maths - Choose the option that gives the solution of the initial-value problem ...

Calculus (Please check my work!) - Suppose that y = f(x) = x^2 - 4x + 4. Then on...

math-Inverse functions - f(x)=-4x-2 & g(x)=5x-6. Find (f*g) and state domain. f(...

PreCalc - What is the real solutions of this equation? sqrt(2x+3)-sqrt(x+2)=2

exprxion - . Simplify the following expressions points) a. sqrt(20) + sqrt(5) b...

Math - Another crazy one... 3sqrt5y^5 divided by 6sqrt20xy For this 3 square ...